A complete durable response of vaginal clear cell carcinoma with pembrolizumab: A case report - Hector S. Porragas-Paseiro; Saketh Guntupalli; Jessie Xiong; Ashley Greenwood (Elsevier, 2023)
Primary clear cell adenocarcinoma of the vagina represents a rare form of cancer historically correlated with in-utero diethylstibestrol (DES) exposure. Mainstay treatment modalities include surgery, radiation, and chemotherapy. There has been a growing interest in immunotherapy in the field of oncology. KEYNOTE 826 demonstrated that patients with persistent, recurrent, or metastatic cervical cancer including patients who had adenocarcinoma showed improved progression and overall survival by the addition Pembrolizumab to chemotherapy plus or minus bevacizumab. To date, there are no documented cases using pembrolizumab as adjuvant treatment for active or recurrent vaginal clear cell adenocarcinoma. We present a case of a young patient with recurrent vaginal clear cell carcinoma who showed a complete and durable response to Pembrolizumab.